Substitution of soybean meal with dried distillery grains on performance and carcass quality of feedlot lambs - Barros Gomes, Helen Fernanda; de Castro, Aruanan Ames; Emmert, Andressa Queiroz; Marques, Raquel Ornelas [UNESP]; Gonçalves, Heraldo Cesar [UNESP]; Brito, Evelyn Prestes [UNESP]; de Lima Meirelles, Paulo Roberto [UNESP]; Correa, Hugo Lennon [UNESP] (My University, 2020)
The objective of this work was to evaluate the effect of inclusion of dried distillery grains (DDGS) as a replacement for soybean meal in the diet of lambs in feedlot and to evaluate the performance, yield characteristics, and meat quality. Three diets with different DDGS levels were provided: diet with soybean meal (control); diet with 50% replacement of soybean meal by DDGS; diet with 100% replacement of soybean meal with DDGS. The average feed intake of the animals and the difference between the leftovers showed no difference among the treatments. No differences of average daily weight gain, body score and feed conversion index were observed among treatments. The same was observed for biometric measurements. However, warm carcass weight and chest perimeter were higher without the use of DDGS. The final weight, muscle, bone, intermuscular, subcutaneous and total fat weight did not differ among treatments. No difference was also found for tissues color. The kilogram of the concentrate mixture that uses soybean meal as the main source of protein (control) was approximately 12% more expensive than the mixture using DDGS (100%). The use of DDGS as an alternative source in confined lamb feeding may be recommended in up to 24% replacement in dietary dry matter.
Influência da substituição do farelo de soja por grão seco de destilaria no desempenho e características de carcaça de ovinos confinados
Keywords: Co-products; Economic cost; Protein source; Supplementation; Young sheep